The Pattern of Community Service on Faculty of Tarbiyah and Teacher Training Lecturers - Munadi, Muhammad; Junanto, Subar; Wahyuningsih, Retno (Jurnal Penelitian, 2019)
Abstract The objectives of this research are to see the pattern of Faculty of Tarbiyah and Teacher Training lecturers in doing community service, the urgency of the lecturers to choose the pattern of community service as done so far, and the obstacle of community service. This research employed qualitative field method. The subjects of this research were the lecturers of Faculty of Tarbiyah and Teacher Training of IAIN Surakarta. Meanwhile, the research informants were the officials in Faculty of Tarbiyah and Teacher Training environment whose leading sector was community services and the community around the lecturers who did community services. Research data was gathered through interview methods, observation and documentation. Data triangulation was done to validate the data. Data obtained from these methods were analyzed interactively. Patterns that can be used in doing community service in Faculty of Tarbiyah and Teacher Training and IAIN Surakarta is the pattern of Czuba, which is divided into 5 areas of community services. They are: engage contacts with individuals, groups and organizations thus can benefit the expertise of the university, contribute to the spiritual growth of the society, offering teaching services and research services, expertise exchange, providing access to facilities and / or programs, as well as special services related to the charter, vision, mission, goals and objectives of the university.Keywords: Community service; Academically Based Community Services (ABCS) pattern;  non Academically Based Community Services (non ABCS) Abstrak Penelitian ini bertujuan mengetahui gambaran pola pengabdian para dosen FITK di lingkungan masyarakatnya, urgensi para dosen memilih pola pengabdian seperti yang dilakukan selama ini, dan kendala pengabdian pada masyarakat. Metode penelitian ini menggunakan metode kualititatif lapangan. Subjek penelitian ini adalah dosen Fakultas Ilmu Tarbiyah dan Keguruan IAIN Surakarta. Sedangkan informan penelitian adalah pejabat di lingkungan FITK yang leading sectornya adalah pengabdian masyarakat dan warga masyarakat sekitar dosen tersebut melakukan pengabdian.Data penelitian akan dikumpulkan melalui metode wawancara, observasi dan dokumentasi. Teknik pemeriksaan keabsahan data menggunakan triangulasi. Data yang diperoleh dari beberapa metode tersebut akan dianalisis secara interaktif. Hasil penelitian ini menunjukkan bahwa Pola yang dipakai dalam pengabdian masyarakat di FITK dan IAIN Surakarta dengan pola Czuba, yang membagi menjadi 5 bidang pengabdian masyarakat yaitu:  Terlibat kontak dengan individu, kelompok dan organisasi sehingga bisa berbagi manfaat dan dan  keahlian yang dimiliki universitas, berkontribusi terhadap pertumbuhan rohani masyarakat, penawaran layanan fungsi pengajaran, dan penelitian, pertukaran keahlian, penyediaan akses ke fasilitas dan/atau program, serta layanan khusus yang berkaitan dengan piagam, visi, misi, tujuan dan sasaran universitas.Kata Kunci: Pengabdian kepada masyarakat; pengabdian masyarakat berbasis akademik; pengabdian masyarakat berbasis non akademik.